2011
DOI: 10.1371/journal.pone.0029019
|View full text |Cite
|
Sign up to set email alerts
|

Optical Dissection of Neural Circuits Responsible for Drosophila Larval Locomotion with Halorhodopsin

Abstract: Halorhodopsin (NpHR), a light-driven microbial chloride pump, enables silencing of neuronal function with superb temporal and spatial resolution. Here, we generated a transgenic line of Drosophila that drives expression of NpHR under control of the Gal4/UAS system. Then, we used it to dissect the functional properties of neural circuits that regulate larval peristalsis, a continuous wave of muscular contraction from posterior to anterior segments. We first demonstrate the effectiveness of NpHR by showing that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 45 publications
11
78
1
Order By: Relevance
“…Positive feedback may still be used to align ongoing neural motor control signals with the mechanics of the body and environment. This is consistent with the observation that waves of muscle activation travel slower in larvae which have been experimentally deprived of mechanosensory input [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Positive feedback may still be used to align ongoing neural motor control signals with the mechanics of the body and environment. This is consistent with the observation that waves of muscle activation travel slower in larvae which have been experimentally deprived of mechanosensory input [18,19].…”
Section: Discussionsupporting
confidence: 91%
“…Light may also distract the animal, perhaps eliciting increased locomotion (Godsil and Fanselow 2004) or encouraging the use of a visual distractor to mask the optogenetic stimulus (Huber et al 2008). Choosing wavelengths of light that the animal cannot see, or is less responsive to, may ameliorate this (Inada et al 2011;Klapoetke et al 2014), as can usage of animals that are engineered to be insensitive to light (Kocabas et al 2012).…”
Section: Heat and Lightmentioning
confidence: 99%
“…Next, we evaluated the effectiveness of optogenetic inhibition of neural activity in living flies with pan-neuronal expression of NpHR, which is a yellow light-driven pump specific for chloride ions (22,(35)(36)(37). With continuous yellow laser irradiation of the head or thorax, we found that experimental flies fed with alltrans-retinal exhibited an anesthesia rate positively correlated with laser energy and that most flies fainted after 60 s or 400 s laser irradiation at 34 or 23 mW/mm 2 , respectively (Fig.…”
Section: Significancementioning
confidence: 99%
“…Recent advances in the optogenetic manipulation of neural activity at the millisecond time scale by using light-activated channelrhodopsin-2 (ChR2) excitation or halorhodopsin (NpHR) inhibition have made it possible to study how neural circuits control behavior (18)(19)(20)(21)(22)(23). Combining online image analysis and two lasers for acute punishment and optogenetic manipulation of selective neural activities, this automatic laser tracking and optogenetic manipulation system (ALTOMS) can precisely specify the timing of the purported associated events (antecedent conditions and response-dependent outcome), which could not be done in previous studies; this ability gives us better experimental control over courtship conditioning and an automated platform to systematically identify the neural circuits responsible for specific Drosophila behaviors.…”
mentioning
confidence: 99%